2019
DOI: 10.1001/jamapsychiatry.2019.1842
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjunctive Estradiol on Schizophrenia Among Women of Childbearing Age

Abstract: IMPORTANCE Several lines of evidence suggest that estradiol influences the course of schizophrenia, and a previous randomized controlled trial demonstrated that transdermal estradiol improved symptoms in female patients of childbearing age. However, many initial positive findings in schizophrenia research are not later replicated. OBJECTIVE To independently replicate the results of the effect of estradiol on schizophrenia in women of childbearing age. DESIGN, SETTING, AND PARTICIPANTS An 8-week randomized, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 32 publications
0
23
0
1
Order By: Relevance
“…Meta-analyses of double-blind RCTs of adjunctive treatment with oestrogen or the selective oestrogen receptor modulator raloxifene (Heringa et al, 2015;de Boer et al, 2018) in women have reported an improvement in positive, negative and total symptom scores with a small to moderate effect size. These findings were replicated by an RCT of the adjunctive use of an oestradiol patch in premenopausal women, but only in a subset of 100 women aged over 38 years (Weiser et al, 2019b). Whether positive results relate to anti-inflammatory or endocrine effects has yet to be established.…”
Section: Oestrogensmentioning
confidence: 96%
“…Meta-analyses of double-blind RCTs of adjunctive treatment with oestrogen or the selective oestrogen receptor modulator raloxifene (Heringa et al, 2015;de Boer et al, 2018) in women have reported an improvement in positive, negative and total symptom scores with a small to moderate effect size. These findings were replicated by an RCT of the adjunctive use of an oestradiol patch in premenopausal women, but only in a subset of 100 women aged over 38 years (Weiser et al, 2019b). Whether positive results relate to anti-inflammatory or endocrine effects has yet to be established.…”
Section: Oestrogensmentioning
confidence: 96%
“…Recent clinical studies have demonstrated that adjunct treatment with 17βestradiol and estrogen-based compounds ameliorate positive, negative and cognitive symptoms experienced by patients diagnosed with schizophrenia or depression [29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has suggested that DISC1 forms aggregates under physiological and pathological conditions 34,41,42 . The formation of aggregates has been proposed to contributes to DISC1's cellular function and the cellular pathology associated with the altered expression of this protein 39,46,47 .…”
Section: Acute Treatment With 17β-estradiol Reduces Aggregation Of Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol and the selective estrogen receptor modulator, raloxifene, have been used as augmentation therapy for women with schizophrenia (and sometimes men), lessening symptom severity and, therefore, potentially leading to reduced doses of antipsychotic medication and fewer adverse effects [63,64]. The effectiveness of estrogen has been attributed to its many neuroprotective actions [58,65], one of which is its anti-inflammatory effect.…”
Section: Hormone-related Periodicity In Womenmentioning
confidence: 99%